Comunicación con padres y el nivel de autoestima en adolescentes de Florencia de Mora - Castañeda Rojas, Keiko Sofía (2019)
The present investigation of correlational descriptive type was carried out in the Educational Institution Tupac Amaru II in Florencia de Mora, 2018, with the purpose of determining the relationship that exists between the type of communication parents-adolescent children and the level of self-esteem. The sample consisted of 148 adolescents. The collection of data was done through two instruments: Coopersmith Self-Esteem Inventory and Barnes and Olson's Parental Communication Scale with Adolescent Sons. Chi square was used to determine the relationship between the variables. The results indicated that 75 percent of the adolescents who presented negative communication with the father and 68.9 percent negative communication with their mother. Regarding self-esteem, 48.7 percent of adolescents showed low self-esteem and 32.4 percent low self-esteem. There is a significant relationship between the type of communication parents - adolescent children and the level of self-esteem.